Approaches to implementation of the plan of action for science and technology for the Caribbean : information aspects of technology transfer, adaptation and innovation ([s.n.] [S.l.])
Examines the question of technology information services to small-scale enterprises in the Caribbean and identifies necessary actions for improving the situation.
Draft